A comparison between chocolate milk and a raw milk honey solution`s influence on delayed onset of muscle soreness - Hatchett, A.; Berry, C.; Oliva, C.; Wiley, D.; St. Hilaire, J.; LaRochelle, A. (Sports, 2016)
This investigation sought to examine the effect that a chocolate milk solution (CMS) and a raw milk solution (RMS) had on lower extremity induced delayed onset of muscle soreness (DOMS). Twenty trained male participants completed a set of questionnaires, prior to completing a lower extremity DOMS protocol, to determine the level of discomfort and functional limitations. Once the DOMS protocol was completed, participants were randomly assigned to either the CM or RM group. Once assigned, participants ingested 240 mL of the respective solution and completed the same set of questionnaires immediately post, 24-, 48- and 72-h post DOMS protocol. Additionally, for 10 days post-ingestion participants were contacted to learn if any negative effects were experienced as a result of ingesting either solution. Both groups reported an increase in lower extremity discomfort at each data collection interval post-DOMS protocol (post, 24-, 48- and 72-h). Participants assigned to the RM group reported high discomfort post and a relative decline in discomfort from immediately post-DOMS protocol to 72-h post. The RMS group reported substantially less discomfort at 72-h when compared to the CMS group. Ingestion of a raw milk solution immediately post strength exercise can substantially reduce the level of self-reported discomfort associated with DOMS.